2022
DOI: 10.1088/1742-6596/2214/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity and space weather

Abstract: After providing an overview of solar activity as measured by the sunspot number (SSN) and space weather events during solar cycles (SCs) 21-24, we focus on the weak solar activity in SC 24. The weak solar activity reduces the number of energetic eruptions from the Sun and hence the number of space weather events. The speeds of coronal mass ejections (CMEs), interplanetary (IP) shocks, and the background solar wind all declined in SC 24. One of the main heliospheric consequences of weak solar activity is the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Toward the end of this cycle, an intense storm has been observed on 26 August 2018 with a Dst index of −175 nT. Only two storms in solar cycle 24 are stronger than this event: The 17 March 2015 (−222 nT) and 23 June 2015 (−204 nT) storms (see e.g., Gopalswamy, Akiyama, et al., 2015; Liu et al., 2015; Webb & Nitta, 2017; Wu et al., 2016). The 26 August 2018 event is characterized by weak solar eruption, significant flux rope rotation in the corona and interplanetary (IP) medium, and an intense geomagnetic storm, as first reported by Chen et al.…”
Section: Introductionmentioning
confidence: 96%
“…Toward the end of this cycle, an intense storm has been observed on 26 August 2018 with a Dst index of −175 nT. Only two storms in solar cycle 24 are stronger than this event: The 17 March 2015 (−222 nT) and 23 June 2015 (−204 nT) storms (see e.g., Gopalswamy, Akiyama, et al., 2015; Liu et al., 2015; Webb & Nitta, 2017; Wu et al., 2016). The 26 August 2018 event is characterized by weak solar eruption, significant flux rope rotation in the corona and interplanetary (IP) medium, and an intense geomagnetic storm, as first reported by Chen et al.…”
Section: Introductionmentioning
confidence: 96%
“…Most models have been developed and validated on events that occurred during specific phases of a specific solar cycle, with the bulk of the model validation and parameters testing work done during cycle 23. It is well known that substantial differences in the physical properties of the solar wind populating the heliosphere during different solar cycles may exist (see e.g., Gopalswamy, 2006; Gopalswamy et al., 2022; Gopalswamy, Xie, et al., 2015; Gopalswamy, Yashiro, et al., 2015; Michalek et al., 2022, and references therein). Therefore, permanent assessment of the solar cycle variations, regarding in particular the background solar wind, needs to become an integral part of the forecast operations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have shown that the space weather due to CIRs are milder in SC 24 [114,[143][144][145][146]. Gopalswamy et al [144] reported that the number of intense geomagnetic storms caused by CIRs has dropped by 75% in SC 24. Grandin et al [146] report that stream SIR/HSSs are 20-40% less geoeffective during cycle 24 than during SC23.…”
Section: Coronal Holes and Geomagnetic Stormsmentioning
confidence: 99%
“…The severest reduction is in the number of GLEs: 16 in SC 23 vs. just 2 in SC 24 (i.e., an 87% drop). This has been attributed to the reduced acceleration efficiency in the weakened ambient magnetic field, so particles did not attain high energies [55,144]. An additional reason could be the presence of fewer seed particles [188].…”
Section: Solar Cycle Dependence Of Space Weather Consequencesmentioning
confidence: 99%